Problemy pomiaru warunków życia w Polsce i w krajach Unii Europejskiej - Muszyńska, Władysława (Problems of Measurement of Living Conditions in Poland and the EU Countries, 2006)
The article aims at analysing preliminary results of the research showing changes of living conditions in the light of experience gained in the first year of Polish membership in the EU.The paper shows the problems of measurement of living conditions in the macrosocial scale (on the basis of the objective synthetic measure) and in the microsocial scale (on the basis of quantitative surveys carried out by Central Office of Statistics and other research agencies) of other subjective indicators reflecting the opinion of the Polish society now being fully European in its organization.Among the unfavourable elements of living conditions in Poland one has to list: higher infant mortality than in the EU, shorter life expectancy in particular for men, much lower number of women active in the labour market correlated with a low level of employment rate.The paper confirms the point of the necessity of being careful in making use of the results of the survey examining living conditions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 232-249